THE EFFECT OF PRODUCT QUALITY, SERVICE QUALITY, CORPORATE IMAGE AND PERCEIVED VALUE ON CUSTOMER LOYALTY OF B2B TRUCK COMPANY WITH CUSTOMER SATISFACTION AS INTERVENING VARIABLES - Steven Wirajaya; Hotna Marina Sitorus; Yogi Yusuf Wibisono; Daniel Kurniawan; Livia Nathania (International Journal of Economics, Business and Accounting Research (IJEBAR), 2023)
PT X is a multinational B2B automotive company that provides large trucks. Based on truck sales data from 2019 to 2021, PT X has experienced a decrease in truck sales. In July 2021, 2 out of 6 transactions failed because customers preferred to buy trucks from other companies. PT X suspects issues with customer loyalty. This study aims to evaluate customer loyalty levels based on factors influencing them. The research phase begins with the construction of research models and questionnaires containing rating questions on perceived value, product quality, service quality, corporate image, customer satisfaction, and customer loyalty. Questionnaires were distributed to customers who had purchased trucks from PT X between October 2021 and November 2021. Data processing is conducted using the PLS-SEM method to derive research conclusions. Based on the results of data processing, it was found that the factors affecting customer loyalty are product quality, corporate image, and customer satisfaction. Suggestions include a focus on these three factors and improvement in the spare part procurement system, with the hope that customer loyalty levels and truck sales will increase.